THE INFLUENCE OF ZNO NANOPARTICLES ON THE AMINO ACIDS BIOSYNTHESIS AT PIGMENTED YEAST RHODOTORULA GRACILIS CNMN-Y-30 - ALINA BEȘLIU; NADEJDA EFREMOVA (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The research paper provides data about the influence of ZnO nanoparticles (NPs) of size <50 nm on the content of proteins and amino acids at pigmented yeast strain Rhodotorula gracilis CNMN-Y-30. The results have highlighted that concentrations of 1-20 mg·L-1 present an opportunity for application in the technology of cultivation of yeast studied, in terms of increasing the protein quantities by with up to 38 %. Also essential, immunoactive and proteinogenic amino acid content measured in yeast biomass after exposure to ZnO nanoparticles in concentrations of 20- 70 mg·L-1 they increased significantly compared to control values. Thus, it can be concluded that the proteins and amino acid content in the studied strain has been modified depending on the concentrations of NPs.